2014
DOI: 10.1002/ejsp.2049
|View full text |Cite
|
Sign up to set email alerts
|

Is the privacy paradox a relic of the past? An in‐depth analysis of privacy attitudes and privacy behaviors

Abstract: The privacy paradox states that online privacy concerns do not sufficiently explain online privacy behaviors on social network sites (SNSs). In this study, it was first asked whether the privacy paradox would still exist when analyzed as in prior research. Second, it was hypothesized that the privacy paradox would disappear when analyzed in a new approach. The new approach featured a multidimensional operationalization of privacy by differentiating between informational, social, and psychological privacy. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
265
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(291 citation statements)
references
References 50 publications
7
265
0
10
Order By: Relevance
“…Personal information features less prominent in their conception of privacy. Similarly, Dienlin and Trepte (2015) showed that distinguishing between privacy concerns, privacy attitudes, and intentions provided a fruitful way of explaining why people continue sharing information on SNSs regardless of privacy concerns. Here we only looked at the relationship between privacy conceptions and reported concern.…”
Section: Discussionmentioning
confidence: 99%
“…Personal information features less prominent in their conception of privacy. Similarly, Dienlin and Trepte (2015) showed that distinguishing between privacy concerns, privacy attitudes, and intentions provided a fruitful way of explaining why people continue sharing information on SNSs regardless of privacy concerns. Here we only looked at the relationship between privacy conceptions and reported concern.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with characteristic of people at Kohlberg's stage 3, which focuses on fulfilling the interests and expectations of others, on gaining their approval. (4) In this study, the mean score of attitudes toward privacy in SNS between nursing (mean 3.97) and advertising (mean 4.06) students is lower compared with those of American (mean 5.0), Chinese (mean 4.8), and Indian (mean 4.6) young people, (14) although the instrument has no same scale but similar 7-Likert scale.…”
Section: Discussionmentioning
confidence: 55%
“…(4) However, attitude toward privacy concerns in SNS of advertising students was similar with nursing students. In healthcare environment, the moral sensitivity toward privacy of the patient should be increased.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations